Musculoskeletal disorders as underlying cause of death in 58 countries, 1986–2011: trend analysis of WHO mortality database. Issue 1 (December 2017) - Kiadaliri, Aliasghar; Woolf, Anthony; Englund, Martin
Abstract Background Due to low mortality rate of musculoskeletal disorders (MSK) less attention has been paid to MSK as underlying cause of death in the general population. The aim was to examine trend in MSK as underlying cause of death in 58 countries across globe during 1986–2011. Methods Data on mortality were collected from the WHO mortality database and population data were obtained from the United Nations. Annual sex-specific age-standardized mortality rates (ASMR) were calculated by means of direct standardization using the WHO world standard population. We applied joinpoint regression analysis for trend analysis. Between-country disparities were examined using between-country variance and Gini coefficient. The changes in number of MSK deaths between 1986 and 2011 were decomposed using two counterfactual scenarios. Results The number of MSK deaths increased by 67% between 1986 and 2011 mainly due to population aging. The mean ASMR changed from 17.2 and 26.6 per million in 1986 to 18.1 and 25.1 in 2011 among men and women, respectively (median: 7.3% increase in men and 9.0% reduction in women). Declines in ASMR of 25% or more were observed for men (women) in 13 (19) countries, while corresponding increases were seen for men (women) in 25 (14) countries. In both sexes, ASMR declined during 1986–1997, then increased during 1997–2001 and again declined over 2001–2011. Despite decline over time, there were substantial between-country disparities in MSK mortality and its temporal trend. Conclusions We found substantial variations in MSK mortality and its trends between countries, regions and also between sex and age groups. Promoted awareness and better management of MSK might partly explain reduction in MSK mortality, but variations across countries warrant further investigations.